The creation of digitally-mediated Christian migrant communities in Singapore - WOODS, Orlando (Institutional Knowledge at Singapore Management University, 2020)
This chapter explores how digital technologies and religion coalesce to help strengthen and/or weaken the formation of communities. Whilst digital technologies have made it easier than ever before for international migrants to remain connected to the communities they left behind, religion can provide a potent source of belonging for the territorially dislocated. The creation of digitally-mediated migrant communities can enhance this sense of belonging, but complicate it as well. Drawing on 72 in-depth interviews conducted with Christian migrants and Singapore-based clergy, I explore how digital technologies enable the formation of content-based, connection-based and support-based Christian migrant communities. I highlight the ways in which migrants must negotiate the tension between being here and there, and between online and offfline religious praxes.